Capital Market Reaction To The Inaugural Of The Carbon Exchange On Lq45 Low Carbon Leaders Stock In Indonesia (Study of Events on LQ45 Low Carbon Leaders Index Shares) - Farhan Al Azhar Besri; Aimatul Yumna (Journal of Economics, Management and Accounting (JEMA), 2023)
This research aims to analyze how the stock market responded to the event of the inauguration of the Carbon Exchange by the President of the Republic of Indonesia Joko Widodo, with a focus on companies included in the LQ45 Low Carbon Leaders index . This study uses a quantitative approach. The population studied consisted of companies listed on the Indonesian Stock Exchange. The research sample consisted of 27 of the 30 companies in the LQ45 Low Carbon Leaders index sector listed on the Indonesian Stock Exchange. Sampling was carried out using a purposive sampling method, using secondary data obtained through direct inspection on the idx.co.id and Yahoo Finance sites. Data analysis was carried out using descriptive statistical analysis, normality test using Kolmogorov-Smirnov (KS) , and difference tests using the Paired Sample T-Test and Wilcoxon Signed-Rank methods . The results of this study show that there is no significant difference in Average Abnormal Return (AR) and Average Trading Volume Activity (TVA) before and after the event, however there are differences in Abnormal Return (AR) and Trading Volume Activity (TVA) on each day. around the observation.